Modelling of economic thresholds for Rumex obtusifolius L. in intensively used grassland and pasture - Schulz, Thomas (Julius-Kühn-Archiv, 2014)
Broadleaf dock (Rumex obtusifolius L.) is one of most frequently arising problem weed in permanent pasture. Numerous publications concern themselves with biology and ecology whereas little information is available quantifying the economic impacts of dock on forage grass yield and quality. Over the course of several growing seasons experiments were conducted in three pasture locations in Saxony and Thuringia (Germany). Dock infestation, yield proportions, yield of grass and dock and the forage value were measured always. The specific dry matter yield of R. obtusifolius is smaller than from L. perenne. With increasing dock settling the total forage yield is not affected negatively nevertheless. From this a potential increased yield follows after the improving the sward. The yield proportion of dock on the total yield can be reliably estimated over a mathematical function from the ground cover of dock, whereas due to the expanded variability in the size of single plants the number of plants was unsuitable for that. In populations grown up at same location the nutrient value of dock was regularly below the nutrient value of the grass component. An algorithm, based on ground cover of dock, net energy content of the grass component and the total dry matter yield was presented to determine the economic impact of various dock infestation. Including the forage use direction and the milk selling price the theoretically monetary income loss can be calculated when necessarily dock control and reseeding of grass filling the gaps will not be done. Using this model it will be possible to determine specific economic thresholds of dock infestations in permanent pasture under different conditions.